Efficacy and Safety of Saffron Supplementation: Current Clinical Findings. Issue 16 (9th December 2016) - Broadhead, G. K.; Chang, A.; Grigg, J.; McCluskey, P.
Abstract : Saffron ( Crocus savitus ) is a Middle-Eastern herb with strong antioxidant properties. Its major constituents, safranal, crocin, and crocetin, are also antioxidants and bear structural similarities to other well-known natural antixodant substances, such as zeaxanthin. Given the role of oxidative stress in many diseases, considerable interest has been shown into the potential role of saffron supplementation as a treatment for a range of diseases. In vitro and animal studies have provided evidence that saffron and its constituents may be potent therapies for a range of pathologies, including Alzheimer's disease, age-related macular degeneration (AMD) and cardiac ischemia. Whether these findings translate into clinical efficacy, however, has as of yet been incompletely assessed. This makes assessing the role of saffron supplementation in these diseases difficult. Here, we review the current human clinical evidence supporting saffron supplementation as a treatment for a range of pathologies and the underlying science supporting its use.